AUMENTO DE JUBILACIONES Y PENSIONES EN EL IMSS COMO RESULTADO DE LA PANDEMIA, MANEJO DE LA SITUACION ECONOMICA ACTUAL - Ambar Valeria De la Cruz Gutiérrez,; Aída Dinorah García Álvarez, (IJRDO - Journal of Business Management, 2021)
In observation of the economic situation and budget management of the Mexican Institute of Social Security (IMSS), as a result of the pandemic regarding the retirements and pensions of workers or, where appropriate, their families, during the past year 2020 and what takes place this year 2021, was determined to some extent, a moment of disabasoment by IMSS.Because older adults and people with chronic diseases belong to the highest-risk group of the virus, while at the same time the high degree of contagion this virus has, many older workers entitled to apply for retirement from IMSS made the decision to do just that, and exercised the right of retirement; on the other hand, the high number of contagions resulted in a large number of workers' deaths, with a large number of them affiliated to the IMSS, following the death of insured workers who were eligible to exercise pension rights or who already had a pension, as these workers were the main livelihood of their families, these relatives (children, wife or concubine) exercised the right to apply for pensions corresponding to the worker's social security.Since the budget envisaged in the IMSS for 2020 during 2019 did not include the pandemic during that year, IMSS had to make various changes to health models and budget management to try to supply the cash shortfall for pensions and retirements.After the analysis of the financial statements of the IMSS and the statistical records thereof, the budgetary management of the Institute was observed and how this problem was addressed.